2020
DOI: 10.3390/app10238706
|View full text |Cite
|
Sign up to set email alerts
|

A Prospective Study of the Exploitation of Pelagic Sargassum spp. as a Solid Biofuel Energy Source

Abstract: This study presents a prospective study for the potential exploitation of pelagic Sargassum spp. as a solid biofuel energy source. It was carried out in three stages. First we conducted a morphological, physical-chemical, and structural characterization using scanning electron microscopy (SEM), infrared spectroscopy (FTIR), and X-ray diffraction (DRX), respectively. Second we evaluated the material’s functional properties as a solid biofuel based on its calorific value and the quantification of polymeric compo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
17
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 61 publications
3
17
0
1
Order By: Relevance
“…In order to carry out the thermogravimetric analysis (TGA) on Sargassum samples, three stages were selected (Figure 1). The first stage indicated a loss of 12% in mass, in the range of 50 to 150 • C, which is attributed to the loss of water as was reported by Davis et al Al et al [19,36] also found a loss of mass in the range of 8-15% in samples of these same species collected in the Caribbean Sea. The second stage is comprised between 180 to 360 • C with a loss of mass of 35% and is seen in the DTGA curves as two strong peaks at 250 and 320 • C. The overlapping of the peaks indicates the complexity of degradation reaction in this zone that is attributed to the decomposition of hemicellulose and cellulose, respectively.…”
Section: Biomass Composition and Characterizationsupporting
confidence: 70%
“…In order to carry out the thermogravimetric analysis (TGA) on Sargassum samples, three stages were selected (Figure 1). The first stage indicated a loss of 12% in mass, in the range of 50 to 150 • C, which is attributed to the loss of water as was reported by Davis et al Al et al [19,36] also found a loss of mass in the range of 8-15% in samples of these same species collected in the Caribbean Sea. The second stage is comprised between 180 to 360 • C with a loss of mass of 35% and is seen in the DTGA curves as two strong peaks at 250 and 320 • C. The overlapping of the peaks indicates the complexity of degradation reaction in this zone that is attributed to the decomposition of hemicellulose and cellulose, respectively.…”
Section: Biomass Composition and Characterizationsupporting
confidence: 70%
“…The exception is the metallic component beryllium (Be), which may be related to metal adsorption by sargassum algae. Additionally, the EDS results are similar to those found in the research by López-Sosa et al, (2020) [36], due to the presence of the same chemical elements in sargassum stems and leaves from Mexico. The large amount of carbon, calcium, and oxygen elements may be related to the calcite phase [33].…”
Section: Production Of the Mortarssupporting
confidence: 89%
“…Figure 1 shows the characterization by scanning electron microscopy of Sargassumspp, the morphology of the vesicles, stems and leaves is observed. As a result of the chemical analysis, different concentrations are identified, mainly of C, O, Ca, S and K. The large amount of C, Ca and O is associated with the presence of calcite that we have reported in previous investigations and that has been corroborated in scientific literature [1,6]. This compound can be visualized in the structures shown in Figure 1 (c).…”
Section: Resultssupporting
confidence: 69%
“…In recent years, the influx of Sargassum spp. on the coasts of the Mexican Caribbean has increased considerably [1][2][3], generating effects on the marine ecosystem and the tourism sector. Recently, various applications of these algae have been explored, for example energy production, biofertilizers and as a bioconstruction material [1,4].…”
Section: Introductionmentioning
confidence: 99%